MON-084 Hyperosmolar Hyperglycemic State as Initial Presentation of Type 1 Diabetes in Children - D’Ambrosio, Fabiola (J Endocr Soc, 2020)
INTRODUCTION: We present 2 pediatric patients with Hyperosmolar Hyperglycemic State (HHS) at diabetes onset. CASE 1: 3 year old African American female presented to the pediatrician office with a 5 day history of polydipsia, polyuria and emesis. POCT glucose read high and patient was transferred to the PICU. Laboratory studies were significant for serum glucose of 1032 mg/dl, Na 128 mMOL/L (corrected 142mMOL/L), VBG showed pH 7.36, HCO3 20 mMOL/L, Serum osm 331 mOsm/Kg. Patient received a 20ml/kg bolus of 0.9%NaCl, followed by 2 times maintenance IV fluids and glargine 2 units. Glucose dropped from 418 to 122 mg/dl in 3 hours. Due to this Dextrose was added and IVF rate was decreased. CASE 2: 8 year old African American obese male was admitted to the PICU for management of new onset diabetes. He presented with 3 days of flu-like symptoms and worsening drowsiness. Patient had increased consumption of large quantities of sugary beverages due to increased thirst. Laboratory workup: serum glucose of 2309 mg/dl, Na 133 mMOL/L (corrected 168 mMOL/L), pH 7.13, HCO3 10 mMOL/L. Patient was given 30 cc/kg NS bolus followed by an insulin drip of 0.1 u/kg/hour. Repeat studies 3 hours later showed a serum glucose of 1,414 mg/dl, Na 152 mMol/L (corrected 184 mMOL/L), pH 7.19, HCO3 17 mMOL/L, and serum osmolality of 408 mOsm/Kg. IVF were adjusted to correct the water deficit and insulin drip was decreased to 0.05u/kg/hour. DISCUSSION: HHS continues to be a challenging diagnosis due to its low frequency compared with Diabetic Ketoacidosis especially when presenting at a very young age. Most practitioners will mistake the presentation for DKA and start an insulin drip. The early use of insulin is not necessary in the setting of HHS due to the risk of complications. A fast drop in glucose decreases the osmotic pressure and compromises the circulatory status with a higher chance of thromboembolism. In mixed HHS and DKA, the management aligns more with the DKA management but the amount of fluids needed is higher and insulin infusion may cause fast drop of glucose with potential decrease of intravascular volume as in our second patient. It is imperative that the diagnosis of HHS is made early so that the appropriate treatment can be instituted. CONCLUSION: Appropriate fluid administration and delay in insulin administration are key in the management of HHS. The awareness of this possible presentation and the early recognition and appropriate fluid management are needed to improve outcomes. REFERENCE: Zeitler, Phil, et al. “Hyperglycemic Hyperosmolar Syndrome in Children: Pathophysiological Considerations and Suggested Guidelines for Treatment.” The Journal of Pediatrics, vol. 158, no. 1, 2011, doi:10.1016/j.jpeds.2010.09.048